Green-light-responsive metal–organic frameworks for colorectal cancer treatment. Issue 34 (5th April 2022) - Cornell, Hannah D.; Zhu, Yumeng; Ilic, Stefan; Lidman, Naomei E.; Yang, Xiaozhou; Matson, John B.; Morris, Amanda J.
Abstract : A novel green-light-responsive nanoMOF with low toxicity was developed as a drug delivery system. Our material demonstrates photo-controlled degradation, drug release, and cancer cell cytotoxicity. Abstract : Herein, the synthetic methods for preparation of a novel light-responsive metal–organic framework (MOF) UiO-AZB-F are outlined. Upon irradiation with green light, the framework demonstrates controlled release of chemotherapeutic drug cargo with simultaneous breakdown into low toxicity small molecule components.